2002
DOI: 10.4049/jimmunol.169.11.6343
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo IL-10 Production Reactivates Chronic Pulmonary Tuberculosis in C57BL/6 Mice

Abstract: The production of immunosuppressive cytokines, such as IL-10 and TGF-β, has been documented in individuals diagnosed with active tuberculosis. In addition, IL-10 production is increased within the lungs of mice that have chronic mycobacterial infection. Therefore, we hypothesized that the down-regulatory properties of IL-10 might contribute to the reactivation of chronic Mycobacterium tuberculosis infection in mice. To determine the influence of IL-10 on the course of infection, transgenic mice producing incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
218
3
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(244 citation statements)
references
References 52 publications
18
218
3
5
Order By: Relevance
“…One of the possible mechanisms by which Mtbhsp60 blocks IL-12 p40 induction could be through induction of anti-inflammatory mediators like IL-10. The IL-10 cytokine has been shown to inhibit IL-12 p40 induction in macrophages (6,30,31) primarily by targeting the c-Rel transcription factor (32). Therefore, it may be possible that Mtbhsp60 predominantly activates IL-10 production through its interaction with TLR2, which subsequently inhibits c-REL vis à vis IL-12 p40 in activated macrophages (29).We also found that interaction of Mtbhsp60 with TLR4 but not TLR2 resulted in increased production of IL-12 (29).…”
supporting
confidence: 55%
“…One of the possible mechanisms by which Mtbhsp60 blocks IL-12 p40 induction could be through induction of anti-inflammatory mediators like IL-10. The IL-10 cytokine has been shown to inhibit IL-12 p40 induction in macrophages (6,30,31) primarily by targeting the c-Rel transcription factor (32). Therefore, it may be possible that Mtbhsp60 predominantly activates IL-10 production through its interaction with TLR2, which subsequently inhibits c-REL vis à vis IL-12 p40 in activated macrophages (29).We also found that interaction of Mtbhsp60 with TLR4 but not TLR2 resulted in increased production of IL-12 (29).…”
supporting
confidence: 55%
“…4B). A considerable body of evidence indicates that IL-10 diminishes macrophage microbicidal capacity (14)(15)(16)(17). In summary, therefore, infection with CH and CAS2 were associated with a pattern of cytokine secretion that would result in phagocyte deactivation favoring the intracellular survival of bacilli.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying the latter observation is unclear, but may be a reflection of the host's attempt to counter the TNF blockade-induced increase in lung inflammation via the immunosuppressive effect of IL-10 (5, 10). Additionally, C57BL/6 transgenic mice producing increased amounts of IL-10 under control of the IL-2 promoter were shown, in a previous study, to have disorganized granuloma structures and reactivated persistent chronic tuberculosis when aerogenically infected (39). That study suggests that increased pulmonic expression of IL-10 in MP6-XT22-treated mice could adversely affect disease outcome.…”
Section: Resultsmentioning
confidence: 81%